Analysis and Classification of Factors in Formation and Development of Gullies (Shakhen Drainage Basin, South Khorasan Province) - mehdei sagafi; reza esmaeili (جغرافیا و توسعه, 2009)
Gully erosion phenomena are very common in semi- arid climate. They affect large areas with different morphological, pedological and climatic characteristics. The amount of soil wasting  due to gullying has become a very serious problem in the recent decades as it was associated to remarkable depletion of cultivated land in Shakhen drainage basin. Two main types of gullies were identified on the basis of their morphological and hydraulic geometry characteristics: (1) Ephemeral gullies which generally develop on low gradient slopes; and (2) Perennial gullies, formed by deep erosion processes. The objectives are (1) to determine the spatial distribution of these gullies in the study area, (2) to measure their morphological and topographical characteristics and (3) to appoint the factors which are led to their reconstruct and development and transformation. In order to investigate the main causes originating the different types of gullies, environmental conditions data such as: physiographic, geology, soil characteristics, hydrology and land use were collected in the field. The hypotheses on the mechanisms responsible for both ephemeral and perennial gullies development and for their different characteristics are discussed. This study investigates these types of gully under semi - arid climate in the small region of Shakhen drainage basin on South Khorasan province. Field investigations on gully morphology and its constructing processes were carried out in three regions from the study area, representative of different geo-environmental conditions. It is suggested that the gully on the region No.1 land system has been more active and, though initiated by overland flow, has developed to a stage where seepage at the base and banks is now the main process. In the study regions, erosion control efforts should be based on dense ground vegetation to reduce flow velocity on the up land to reduce flow volumes on the area with gully erosion.